2018
DOI: 10.1101/295444
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Earthworms and Cadmium - heavy metal resistant gut bacteria as indicators for heavy metal pollution in soils?

Abstract: Preservation of the soil resources stability is of paramount importance for the ecosystem, particularly in the current era of environmental change, which presents a severe pollution burden (e.g. by heavy metals) to soil ecosystems and its fauna. Gut microbiomes are becoming recognized as important players in organism health, with comprehension of their perturbations in the polluted environment offering new insights into the nature and extent of heavy metal effects on the health of soil biota. Our aim was there… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 85 publications
1
11
0
1
Order By: Relevance
“…Chryseobacterium solincola can grow despite the elevated presence of highly toxic metals and has been suggested as a candidate for the situ bioremediation of heavy metals in aqueous or soil systems (50). Agrobacterium tumefaciens is able to survive in regions containing high levels of heavy metals and possesses various transporters involved in Ni, Cu, Zn and Cr resistance (51,52).…”
Section: Cd-sensitive and Cd-resistant Taxa Were Determined Among Earthworm Gut Microbiotamentioning
confidence: 99%
See 1 more Smart Citation
“…Chryseobacterium solincola can grow despite the elevated presence of highly toxic metals and has been suggested as a candidate for the situ bioremediation of heavy metals in aqueous or soil systems (50). Agrobacterium tumefaciens is able to survive in regions containing high levels of heavy metals and possesses various transporters involved in Ni, Cu, Zn and Cr resistance (51,52).…”
Section: Cd-sensitive and Cd-resistant Taxa Were Determined Among Earthworm Gut Microbiotamentioning
confidence: 99%
“…Metal-polluted soils also strongly influence soil microbiota and the microbiota of soil organisms. Several studies have shown a decrease in microbe biodiversity in metal-polluted soils (3)(4)(5). For instance, Cd inhibits microbial reproduction in soil (6), and Cd, copper (Cu), nickel (Ni), lead (Pb), chromium (Cr), arsen (As) and zinc (Zn) have been found to decrease the biomass, species richness and activity of microbial communities in forest and arable soils (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria are the most abundant microorganisms in the world and their diversity has not yet been completely elucidated [30][31][32][33][34] . In the environmental eld, bacteria have been useful in the analysis of water quality 35,36 , in the evaluation of soil contamination 37,38 , and as the indicators of food quality 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Loss of some core earthworm symbionts can lead to reduced host fitness and juvenile development [ 51 , 52 ]. Environmental pollutants can alter the microbiome of earthworms [ 53 , 54 , 55 , 56 ] and lead to the loss of core symbionts important to host health [ 57 ]. An increasing body of literature now indicates that exposure to NMs can also disrupt the microbiome of soil invertebrates [ 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%